Solubility Enhancement and Characterization of Tamoxifen Citrate Using Co-crystallization - Dolih Gozali; Iyan Sopyan; Hairunnisa Hairunnisa; Siska Sari Marvita (Indonesian Journal of Chemistry, 2022)
Tamoxifen citrate (TC) is one of the anti-estrogen agents which has low solubility in the water. As TC is still used as the main therapy in breast cancer treatment, modifications are still being made to increase the solubility of TC for a successful treatment. In this research, co-crystallization of TC was performed using Nicotinamide (NIC), Isonicotinamide (ISO), Saccharin (SAC), Aspartame (ASP), and Benzoic Acid (BNZ) as a coformer with the molar ratio of 1:1, 1:2, and 2:1. Co-crystal was prepared by solvent drop grinding (SDG) and solvent evaporation (SE) methods using methanol. The results of the solubility test showed that TC-NIC and TC-ISO co-crystals with a 1:2 molar ratio made using the SDG and SE methods gave the best results. Meanwhile, the best dissolution test results were shown by TC-ISO co-crystals with a ratio of 1:2. Based on the characterization of physical stability, the SDG method resulted in more stable TC co-crystals than the SE method. Therefore, in this case, the SDG method could be more advantageous to be used for development in the field of co-crystallization.